Capability Level Analysis of IT Governance Using COBIT 5 on Continuity and Availability Of Services (Case Study: LMS Spada Wimaya) - Dyah Anggraini Kartika Putri; Juwairiah Juwairiah; Frans Richard Kodong (Jurusan Teknik Informatika, 2022)
Purpose: This study aims to assess the capability level to determine the condition of the capability level as-is, to-be, gap analysis and provide recommendations for improving IT governance in the continuity and availability process of LMS Spada Wimaya service. Design/methodology/approach: The capability level assessment refers to the COBIT 5 Process Assessment Model (PAM) assessment criteria with the research stages adopting the COBIT 5 Assessment Process Activities. Findings/result: Based on the urgency and problems that occur in LMS Spada Wimaya related to the continuity of service availability, the appropriate COBIT 5 enterprise goals are chosen, namely Business Service Continuity and Availability which describes in achieving the vision and mission goals of UPN